2002
DOI: 10.1016/s0304-3959(01)00442-0
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular tactile and pain thresholds in women with vulvar vestibulitis syndrome

Abstract: Vulvar vestibulitis syndrome (VVS) is a common cause of dyspareunia in pre-menopausal women. Little is known about sensory function in the vulvar vestibule, despite Kinsey's assertion that it is important for sexual sensation. We examined punctate tactile and pain thresholds to modified von Frey filaments in the genital region of women with VVS and age- and contraceptive-matched pain-free controls. Women with VVS had lower tactile and pain thresholds around the vulvar vestibule and on the labium minus than con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
206
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(231 citation statements)
references
References 51 publications
20
206
3
2
Order By: Relevance
“…Not surprisingly, Pukall found that the vestibular punctate pain pressure thresholds of women suffering from VVS were dramatically lower than those of matched controls (Pukall, Binik, Khalifé, Amsel, & Abbott, 2002; see also Granot, Friedman, Yarnitsky, & Zimmer, 2002). This clearly reflected the clinical phenomenon of VVS.…”
Section: Binikmentioning
confidence: 88%
“…Not surprisingly, Pukall found that the vestibular punctate pain pressure thresholds of women suffering from VVS were dramatically lower than those of matched controls (Pukall, Binik, Khalifé, Amsel, & Abbott, 2002; see also Granot, Friedman, Yarnitsky, & Zimmer, 2002). This clearly reflected the clinical phenomenon of VVS.…”
Section: Binikmentioning
confidence: 88%
“…• Multimodal therapy : Vulvar vestibilitis (VV) should be treated with a combined, multimodal treatment aimed at reducing: a) the up-regulation of mastcells, both by reducing the agonist stimuli (such as candida infections, microabrasions of the introital mucosa because of intercourse with a dry vagina and/or a contracted pelvic floor, chemicals, allergens etc) that cause degranulation leading to chronic tissue inflammation, and/or with antagonist modulation of its hyper-reactivity, with amitryptiline or aliamide's gel [6,42,44]; b) the up-regulation of pain system secondary to both the proliferation of introital pain fibers [25][26][27] induced by the Nerve Growth Factor produced by the upregulated mast-cells, and the lowered central pain threshold [45]. A thorough understanding of the pathophysiology of pain, in its nociceptive and neuropathic component, is essential.…”
Section: ) Medical Treatmentmentioning
confidence: 99%
“…Variables that have discriminated between healthy controls and women with dyspareunia include vulnerability factors, such as the personality trait neuroticism (e.g., Van Lankveld, Brewaeys, ter Kuile, & Weijenborg, 1995), mood disruptions (e.g., Gates & Galask, 2001), underlying psychopathology, such as obsessive-compulsive traits and phobias (e.g., Meana et al, 1997;Van Lankveld et al, 1995), and individual difference factors like catastrophizing and hypervigilance (Payne et al, 2004;Pukall, Binik, Khalifé, Amsel, & Abbott, 2002). However, many of these studies are limited by a lack of control groups and only a few psychological factors have been consistently addressed in the literature (e.g., depression, anxiety).…”
Section: Introductionmentioning
confidence: 99%